Efficacy Of Intravitreal Bevacizumab in the Treatment of Vitreous Hemorrhage Secondary to Proliferative Diabetic Retinopathy - Omer Farooq; Jabbar, Bushra; Asad Habib; Ubaidullah Yasin; Najia Ahmed; Fazla Younis (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the efficacy of intravitreal bevacizumab in the treatment of vitreous hemorrhage secondary to proliferative diabetic retinopathy.Study Design: Quasi-experimental study.Place and Duration of Study: The study was conducted at PNS Shifa Hospital, Karachi Pakistan, from Sep 2018 to Feb 2019.Methodology: The study included 131 patients with proliferative diabetic retinopathy who presented with vitreous hemorrhage. Vitreous hemorrhage was graded into mild-moderate or severe. Patients were randomized into two groups: the bevacizumab group was treated with three intravitreal injections of bevacizumab given on monthly intervals and the control group which was observed. Vitrectomy was performed if the patient had non resolving hemorrhage by four months or developed tractional retinal detachment during study period.Results: Mean age of patients was 51.8±7.4 and 52.6±6.7 in treatment and control group respectively. Percentage of patients with vision of less than 6/60 in treatment group reduced from (58.7%) at baseline to (33%) at 4 months. Patients with mild to moderate VH who were subjected to intravitreal bevacizumab had significantly less chance of undergoing PPV at 4 months (4.76%) as compared with control group (20%). Improvement in visual acuity was also statistically significant at 4 months (p